A New Grafted Cactus with Bright Yellow Color, 'Hwangseon' - Park, P.M., National Institute of Horticultural and Herbal Science, RDA, Suwon, Republic of Korea; Jeong, M.I., National Institute of Horticultural and Herbal Science, RDA, Suwon, Republic of Korea; Yae, B.W., National Institute of Horticultural and Herbal Science, RDA, Suwon, Republic of Korea; Kim, M.S., National Institute of Horticultural and Herbal Science, RDA, Suwon, Republic of Korea; Lee, Y.R., National Institute of Horticultural and Herbal Science, RDA, Suwon, Republic of Korea; Park, P.H., National Institute of Horticultural and Herbal Science, RDA, Suwon, Republic of Korea; Yoo, B.S., National Institute of Horticultural and Herbal Science, RDA, Suwon, Republic of Korea (Weon'ye gwahag gi'sulji, 2012)
A new grafted cactus cultivar, called 'Hwangseon', Gymnocalycium mihanovichii, is a hybrid crossed between two orange color cultivars 'Geoseong' and 'Huhwang'. Mating was performed in the greenhouse of National Institute of Horticultural and Herbal Science (NIHHS) in 2005. The harvested seeds were sown at 100 mL volumetric flasks filled with 'Kyoto' medium. Seedling had been grafted into a young rootstock, Hylocereus trigonus, and cultured in vitro in 100 mL test tube for more than six months. After re-grafting and planting in the green house in 2006, their characteristics were evaluated three times until 2009. The new cultivar has a flat round shape and bright yellow skin color. In addition, it has 7 to 9 ribs with gray and straight spines on the body and produces an average of 12.3 offsets.